Tropical Vegetable Production - George, Raymond A.T (CABI, 2014)
Despite efforts to improve and increase food production and supply by institutional developments during recent decades, there still remains a major food security problem in many parts of the world, especially in the tropics and subtropics. It is now being increasingly recognized and appreciated that a large propor- tion of populations in developing countries are reliant on subsistence farm production for their day-to-day food supply and longer-term food security. This food source is frequently referred to as the ‘informal sector’ of food production. The recognition of this fact was an important outcome of the G8 Conference held in Italy in 2009 and it was also emphasized by President Barack Obama during his address in Accra, Ghana, on 10 July, 2009. The President also stated that ‘Aid is not an end in itself. The purpose of foreign assistance must be creating the conditions where it is no longer needed.’ One of the most important aspects of subsistence farming is the day-to-day availability of fresh and stored vegetables and their products. Despite what has been achieved in the past by national and international programmes it is very apparent that we must do signiﬁ cantly more to ensure that the subsistence farm- ers are able to not only increase their vegetable productivity and food security but that their improved food supply becomes sustainable thereby improving the health, well-being and education of their dependents and overall reduction of poverty. Many of us who have been involved with agronomy and related subjects in tropical environments believe that more effort has to be given to improving food security from the bottom up, that is by improving the informa- tion and material inputs such as improved seed, planting materials and technol- ogy available to small farmers. There is an urgent need for more farmer training and research which is of direct relevance to improving production on the subsistence farms.